UK Library and Information Research Group (CILIP) Research Award 2008 - Editorial Team, (Evidence Based Library and Information Practice, 2007)
The UK Library & Information Research Group (LIRG) research award is designed to promote research in library and information science. The aim of the award is to encourage and facilitate research by practitioners in the field. LIRG welcomes proposals from all sectors of the profession, and particularly invites practitioners to apply either as sole applicants, or in collaboration with academic or independent researchers. Applications from academics in library and information science departments are welcome and proposals that are submitted in partnership with practitioners are particularly welcome. The award is open to applicants from the UK only. The award is worth £1000, and designed to support small-scale research projects for which it may otherwise be difficult to find funding. The award may be used to defray research expenses (e.g. travel, postage costs), to fund attendance at high level meetings or to fund a study tour. However, a clear overall aim for the research must be stated. Guidelines for submission and evaluation criteria are on the LIRG web pages at: http://www.cilip.org.uk/specialinterestgroups/bysubject/research/activities/awards/researchaward.htm The closing date for submissions is February 29th, 2008 Applications and enquiries should be sent, preferably by e-mail, to: Dr Jean Yeoh LIRG Awards and Prizes Coordinator Information Services & Systems King's College London 4th Floor Waterloo Bridge Wing Franklin Wilkins Building 150 Stamford Street London SE1 9NN jean.yeoh@kcl.ac.uk 020 7848 4460